2021
DOI: 10.2217/fon-2021-1406
|View full text |Cite
|
Sign up to set email alerts
|

INSIGHT 2: a Phase II Study of Tepotinib Plus Osimertinib in MET -Amplified NSCLC and First-Line Osimertinib Resistance

Abstract: MET amplification (METamp), a mechanism of acquired resistance to EGFR tyrosine kinase inhibitors, occurs in up to 30% of patients with non-small-cell lung cancer (NSCLC) progressing on first-line osimertinib. Combining osimertinib with a MET inhibitor, such as tepotinib, an oral, highly selective, potent MET tyrosine kinase inhibitor, may overcome METamp-driven resistance. INSIGHT 2 (NCT03940703), an international, open-label, multicenter Phase II trial, assesses tepotinib plus osimertinib in patients with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 62 publications
1
31
0
1
Order By: Relevance
“…For patients with MET-mediated resistance to osimertinib, savolitinib plus osimertinib is currently being assessed prospectively in the ongoing SAVANNAH ( 31 ), ORCHARD ( 43 ), and SAFFRON (NCT05261399) studies, and tepotinib plus osimertinib is being assessed in the INSIGHT2 study (NCT03940703; ref. 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with MET-mediated resistance to osimertinib, savolitinib plus osimertinib is currently being assessed prospectively in the ongoing SAVANNAH ( 31 ), ORCHARD ( 43 ), and SAFFRON (NCT05261399) studies, and tepotinib plus osimertinib is being assessed in the INSIGHT2 study (NCT03940703; ref. 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another phase 1b/2 study (NCT02468661) investigating the safety and efficacy of capmatinib alone or in combination with erlotinib vs chemotherapy in patients with advanced EGFRm NSCLC with MET amplification was terminated due to enrollment issues. An identical effort is ongoing with the phase 2 INSIGHT-2 trial (NCT03940703) investigating tepotinib, a highly selective MET inhibitor, in combination with osimertinib for patients with advanced EGFRm NSCLC and MET amplification [93].…”
Section: Met-targeted Therapiesmentioning
confidence: 99%
“…A study fully illustrated the role of Hh signaling in EGFR mutant lung cancer, their result showed that, through the induction of mesenchymal properties, Hh could mediate the resistance of EGFR inhibitors (110). Several clinical studies reported acquired resistance to targeted drugs, such as Osimertinib, a MET tyrosine kinase inhibitor (111). The advance in K-RAS targeted medicine faced huge challenge (112).…”
Section: Met Mutationsmentioning
confidence: 99%